(3TQGFY GdESdGes - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdWgGQI, GdWgGQI GSe ddhVhA Ch GdZSd Gh GdJjee Ydi hLg dg (B.. (3aj GSJHGMI GdUdhI hcd hGMO efgG jfbSe Edi hGLH hfOH, aGdhGLH ef GdhVhA eG cGf ddUdGIs
(3BNQgG (B:s
(3BNQgG(B: (3hdMH QShdg Udi Gddg Ydjg hSde Ydi GdJeSc Hge hGdYed HSfJge MJi bQfge HGdcJGH GdeLjO GdPj dG jCJjg GdHGWd Hjf jOjg hdG ef Ndags
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 123s
(3GdPQjYI, L (B13: 30s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis